Digital-маркетинг як технологія просування органічної продукції - Новицька, І.В. (Вісник економічної науки України, 2019)
У статті виділяється використання digital-маркетингу, як можливості сучасного просування органічної продукції, що повинно перетворитися в комплекс різноспрямованих складових, таких як: глибоке вивчення онлайн-аудиторії, її поведінкової складової; залучення всіх можливих сегментів аудиторії; занурення співробітників виробництва продукції в цифрову комунікацію з споживачем; організація взаємодії з потенційним споживачем. Digital-технологія забезпечує комплексний підхід до просування органічної продукції в цифровому середовищі, що охоплює також офлайн споживачів, які використовують мобільні телефони та інші цифрові засоби зв'язку. Надає можливість інтеграції великої кількості різних технологій (соціальні, мобільні, веб тощо) з продажами і клієнтським сервісом; постійний якісний двосторонній зв'язок між рекламодавцем і кінцевим споживачем органічної продукції; поєднання технологій і людських ресурсів, дотримуючись правильного балансу, виходячи з потреб цільової аудиторії і особливостей пропонованої органічної продукції; можливість бути релевантним ринку, оцінювати і аналізувати результати просування, гнучко реагувати на потреби ринку. В статье выделяется использование digital-маркетинга, как возможности современного продвижения органической продукции, что должно превратиться в комплекс разнонаправленных составляющих, таких как: глубокое изучение онлайн-аудитории, ее поведенческой составляющей; привлечение всех возможных сегментов аудитории; погружение сотрудников производства продукции в цифровую коммуникацию с потребителем; организация взаимодействия с потенциальным потребителем. Digital-технология обеспечивает комплексный подход к продвижению органической продукции в цифровой среде, охватывающей также оффлайн потребителей, использующих мобильные телефоны и другие цифровые средства связи. Предоставляет возможность интеграции большого количества различных технологий (социальные, мобильные, веб и т.д.) с продажами и клиентским сервисом; постоянную качественную двустороннюю связь между рекламодателем и конечным потребителем органической продукции; сочетание технологий и человеческих ресурсов, соблюдая правильного баланса, исходя из потребностей целевой аудитории и особенностей предлагаемой органической продукции; возможность быть релевантным рынка, оценивать и анализировать результаты продвижения, гибко реагировать на потребности рынка. The article highlights the use of digital marketing as an opportunity for modern promotion of organic products, which should turn into a complex of multidirectional components, such as: a deep study of the online audience, its behavioral component; Engaging all possible audience segments immersion of production employees in digital communication with the consumer; organization of interaction with the potential consumer. Digital technology provides an integrated approach to promoting organic products in the digital environment, also encompassing offline consumers using mobile phones and other digital communications. Provides the ability to integrate a large number of different technologies (social, mobile, web, etc.) with sales and customer service. Continuous quality two-way communication between the advertiser and the end consumer of organic products; the combination of technology and human resources, keeping the right balance, based on the needs of the target audience and the features of the organic products offered; the ability to be relevant to the market, evaluate and analyze the results of promotion, respond flexibly to market needs. The article notes that digital marketing is more profitable than a traditional advertising campaign, especially for small non-network manufacturers. Organic producers who previously could not afford to compete with the big players side by side with the big players are now offered to launch a quality campaign for their audience, even at low marketing costs. marketing opens up a lot of new opportunities for organic businesses, while improving the quality of ordering and delivery and making it more personalized to potential consumers.